PROBLEMATIKA PEMBELAJARAN AL-QUR’AN DI ERA INDUSTRI DALAM KONTEKS INDONESIA - Dewi Ratnawati; Ahmad Zainal Abidin; Eko Zulfikar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
There are at least two factors that trigger problems in the Qur`an learning in the industrial era 4.0: the rejection of changes that occur in educators and acceptance of changes, but the available technological infrastructure cannot support learning of the Qur`an into the realm of education in the era industry 4.0. This resulted in failure in learning the Qur`an. The manifestations of this failure are in the form of unsuccessful character building for students to have Qur`anic characters, fading love of students for the Qur`an, loss of students' polite behavior, and limited material received only limited to cognitive knowledge without performance abilities. By using the descriptive-explorative method, this paper produces findings that the problems of learning the Qur`an in the industrial era, namely: the use of the Qur`an learning method which is monotonous, the learning strategy of the Qur`an is not yet right, the lack of facilities. infrastructure that supports learning Qur`an, there has not been any transformation and innovation of the Qur`an learning that takes advantage of technological sophistication, the lack of professional educators, and lack of support from the environment for the realization of a triple education center.